Bio-fabrication of gold nanoparticles using aqueous extract of red tomato and its use as a colorimetric sensor - Barman, Gadadhar (Springer, 2013)
In this work, we report a green method for the synthesis of gold nanoparticles (GNP) using the aqueous extract of red tomato (Lycopersicon esculentum). We believe that citric acid and ascorbic acid present in tomato juice are responsible for the reduction of gold ions. This biosynthesized GNP in the presence of sodium dodecyl sulfate has been used as a colorimetric sensor to detect and estimate the pesticide, methyl parathion. The GNP in the presence of methyl parathion shows a new peak at 400 nm due to the formation of 4-nitrophenolate ion by catalytic hydrolysis of methyl parathion in alkaline medium. A calibration curve between the absorption coefficients of the 400-nm peak versus the concentration of the pesticide allows the quantitative estimation of the 4-nitrophenolate ion, thereby enabling indirect estimation of methyl parathion present in the system.